(untitled) (Clinics, 2008)
OBJECTIVE: The aim of this study was to investigate the presence of growth hormone receptor in plexiform neurofibromas of neurofibromatosis type 1 patients. INTRODUCTION: The development of multiple neurofibromas is one of the major features of neurofibromatosis type 1. Since neurofibromas commonly grow during periods of hormonal change, especially during puberty and pregnancy, it has been suggested that hormones may influence neurofibromatosis type 1 neurofibromas. A recent study showed that the majority of localized neurofibromas from neurofibromatosis type 1 patients have growth hormone receptor. METHODS: Growth hormone receptor expression was investigated in 5 plexiform neurofibromas using immunohistochemistry. RESULTS: Four of the 5 plexiform neurofibromas were immunopositive for growth hormone receptor. CONCLUSION: This study suggests that growth hormone may influence the development of plexiform neurofibromas in patients with neurofibromatosis type 1.